Clinical correlates of epistaxis management in ENT emergency - Vivek Kumar (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2020)
Introduction: Epistaxis is a frequent condition encountered in an ENT emergency which causes severe anxiety to the patient. Management of epistaxis may become challenging and can necessitate urgent intervention.  Objective: To analyze the clinical correlates of nasal bleeding in an ENT emergency setting. Type of study: Retrospective study. Materials and methods: Data was collected from the ENT emergency register, ward registers and case notes of patients presenting with nasal bleeding to the emergency at an urban tertiary health care center in India for a period of 1 year. Data acquired was reviewed and statistically interpreted and presented in graphical and descriptive formats.  Results: We encountered 204 cases of epistaxis in the ENT emergency over the period under study. Cardiovascular complaints (hypertension and atherosclerosis) were the commonest causes of nasal bleeding in the study population. There was a seasonal preponderance for winter months. Significant correlation was observed between the site of bleeding and the management accorded to the patient. Advances in endoscopic facility and imaging modalities contributed immensely to the management.  Conclusion: Epistaxis management protocol should be based on etiology, age, site and severity of nasal bleeding and in accordance with facilities available at the centre. Active and meticulous search for cause of nasal bleeding should be performed. Training of residents in conservative treatment approaches should be done under proper guidance.